STRATEGI PUBLIC RELATION ABICANDRA ABIASA FISIP DALAM MENARIK SPONSOR MELALUI BRANDING DI INSTAGRAM - Selfi Lestari; Angelina Meylani Putri; Abdurrahman (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This paper discusses the Public Relation (PR) strategies implemented by Abicandra Abiasa FISIP in attracting sponsors through branding activities on Instagram. In today’s fast-paced digital era, social media has become an effective communication medium for organizations to build their image and expand networks, including establishing partnerships with external parties such as sponsors. The purpose of this paper is to identify how Abicandra Abiasa FISIP utilizes communication strategies through its Instagram account to create attractive branding, and how these strategies influence sponsors’ interest in supporting organizational activities. This study uses a qualitative descriptive method, with data collected through social media observation, interviews with the organization’s public relations division, and literature studies related to communication and Public Relations theories. The results show that Abicandra Abiasa FISIP’s branding strategy focuses on visual consistency, informative and interactive message delivery, and strengthening the organization’s positive image. Through these approaches, the organization successfully builds public trust and attracts sponsors to collaborate in various activities.